Universal method for calculation of reliable completion times - Yu.B. Kalugin (Инженерно-строительный журнал, 2016)
Usually the actual duration of construction projects significantly exceeds the scheduled durations.The reason is the lack of realistic scheduling. This paper presents a universal method for computing the reliable completion time for a construction project with network plans that have imprecise durations. The study is based on the consecutive comparison and calculation of the time distributions for the fulfilment of construction events. The general applicability of the algorithm is demonstrated. The method was used for the calculation of a more realistic time span for the construction of a road. The network schedule is formed on the basis of the flow sheet. A comparison was drawn between the proposed method and traditional techniques. The mean duration of the technological process calculated by a universal method is 30% more than for a known critical path method. It is confirmed that the traditional method of calculating the time to complete a project is almost always shorter. The method and algorithm presented in this study used Microsoft Excel. The calculations lasted some seconds. Implementation of the universal method will allow for the determination of a more precise duration for the performance of complex works at the planning stage.The suggested methodology can be recommended for use by construction project managers.